Image-Guided Surgery in Patients with Pancreatic Cancer: First Results of a Clinical Trial Using SGM-101, a Novel Carcinoembryonic Antigen-Targeting, Near-Infrared Fluorescent Agent - Hoogstins, Charlotte E. S. (Ann Surg Oncol, 2018)
BACKGROUND: Near-infrared (NIR) fluorescence is a promising novel imaging technique that can aid in intraoperative demarcation of pancreatic cancer (PDAC) and thus increase radical resection rates. This study investigated SGM-101, a novel, fluorescent-labeled anti-carcinoembryonic antigen (CEA) antibody. The phase 1 study aimed to assess the tolerability and feasibility of intraoperative fluorescence tumor imaging using SGM-101 in patients undergoing a surgical exploration for PDAC. METHODS: At least 48 h before undergoing surgery for PDAC, 12 patients were injected intravenously with 5, 7.5, or 10 mg of SGM-101. Tolerability assessments were performed at regular intervals after dosing. The surgical field was imaged using the Quest NIR imaging system. Concordance between fluorescence and tumor presence on histopathology was studied. RESULTS: In this study, SGM-101 specifically accumulated in CEA-expressing primary tumors and peritoneal and liver metastases, allowing real-time intraoperative fluorescence imaging. The mean tumor-to-background ratio (TBR) was 1.6 for primary tumors and 1.7 for metastatic lesions. One false-positive lesion was detected (CEA-expressing intraductal papillary mucinous neoplasm). False-negativity was seen twice as a consequence of overlying blood or tissue that blocked the fluorescent signal. CONCLUSION: The use of a fluorescent-labeled anti-CEA antibody was safe and feasible for the intraoperative detection of both primary PDAC and metastases. These results warrant further research to determine the impact of this technique on clinical decision making and overall survival.